FOREIGN COMMUNICATIVE COMPETENCE ASSESSMENT SYSTEM OF STU-DENTS OF NON-LINGUISTIC UNIVERSITIES AS A PEDAGOGICAL PROBLEM - Maria M. Malova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The main problem of the assessment system of foreign communicative competence of students of non-linguistic universities is increasing of students’ motivation to the learning process, formation of their knowledge, abilities and skills and competence acquirement. The solving of this pedagogical problem can be achieved through the establishment of feedback between a teacher and students, when their full interaction is possible provided that the structure of assessment system corresponds to the principle of consistency. The research of this pedagogical problem requires presenting the assessment process in the form of a system. Thus the aim of the given research is analyzing and considering how the as-sessment system of foreign communicative competence of students of non-linguistic universi-ties is organized. In the process of investigation it is necessary to prove if the assessment sys-tem corresponds to the notion of a “system”, define the components of the system and trace the relationship between them. The analysis of the assessment system of foreign communicative competence of students of non-linguistic universities has been based on the following approaches: system, competence-based, communicative, individual, data-technological and vocationally-orientated. The analysis of the approaches considered has revealed the system nature of assessment, has defined the structure of the system and has showed that assessment is an inseparable system, including the teacher and students connected by the feedback principle, methods and means of assessment and students’ knowledge, abilities, skills and competences. The approaches to the assessment of foreign communicative competence of students of non-linguistic universities are given in the form of hierarchy because their detailed analysis has shown a certain relationship between them. Reviewing the assessment system through each of the approaches we can argue that all the approaches in the hierarchy are placed according to the extent of their importance. System approach is at the top of the hierarchy for it is the system approach that considers an object as a system; therefore it is fundamental in the study of the assessment system. The system approach deals with interrelated objects inside a system, the system that has a purpose, connection with outside environment and feedback - all the characteristics that are inherent in the assessment system.